The African swine fever virus gene MGF_360-4L inhibits interferon signaling by recruiting mitochondrial selective autophagy receptor SQSTM1 degrading MDA5 antagonizing innate immune responses - Hualin Sun; Jifei Yang; Zhonghui Zhang; Mengli Wu; Zhancheng Tian; Ying Liu; Xiaoqiang Zhang; Jianhao Zhong; Songlin Yang; Yikang Chen; Jianxun Luo; Guiquan Guan; et al. (mBio)
ABSTRACT Multigene family (MGF) 360 genes, which are African swine fever virus (ASFV) virulence genes, primarily target key host immune molecules to suppress host interferon (IFN) production and interferon-stimulated gene (ISG) transcription, impairing host innate immune responses for efficient viral replication. However, the interactions between MGF 360 virulence genes and host molecules, as well as the mechanisms through which MGF 360 genes regulate host immune responses and IFN signaling, require further elucidation. In this study, we discovered that ASFV MGF_360-4L interacts with MDA5 and recruits the mitochondrial selective autophagy receptor SQSTM1 to degrade MDA5, thus impairing IFN signaling and compromising host innate immune responses. Furthermore, MGF_360-4L inhibits the interaction between MDA5 and MAVS, blocking ISG15-mediated ISGylation of MDA5. MGF_360-4L deficiency significantly attenuated virus-induced mitochondrial autophagy in vitro. Additionally, OAS1 ubiquitinates MGF_360-4L at residues K290, K295, and K327. Finally, a recombinant ASFV lacking the MGF_360-4L gene (ASFV-∆MGF_360-4L) was generated using ASFV-CN/SC/2019 as the backbone, which demonstrated that the replication kinetics of ASFV-∆MGF_360-4L in PAM cells were like those of the highly virulent parental ASFV-WT in vitro. Domestic pigs infected with ASFV-∆MGF_360-4L exhibited milder symptoms than those infected with parental ASFV-WT, and ASFV-∆MGF_360-4L-infected pigs presented with enhanced host innate antiviral immune response, confirming that the deletion of the MGF_360-4L gene from the ASFV genome highly attenuated virulence in pigs and provided effective protection against parental ASFV challenge. In conclusion, we identified a novel ASFV virulence gene, MGF_360-4L, further elucidating ASFV infection mechanisms and providing a new candidate for vaccine development.IMPORTANCEAfrican swine fever virus (ASFV) infection causes acute death in pigs, and there is currently no effective vaccine available for prevention. Multigene family (MGF) virulence genes have been shown to be crucial for ASFV’s ability to evade host innate immune responses. However, the functions of most MGF genes remain unknown, which poses significant challenges for the development of ASFV vaccines and antiviral drugs. In this study, we identified a virulence gene of ASFV, MGF_360-4L, that targets and recruits the selective autophagy receptor p62 to mediate the degradation of the dsRNA sensor MDA5, thereby blocking interferon signaling. Additionally, it inhibits the ISG15-mediated ISGylation activation of MDA5. ASFV lacking MGF_360-4L showed reduced virulence and provided protection in pigs. Our data identify a novel virulence gene and provide new insights for ASFV vaccine development.